Navigating Preparedness for CSDDD Compliance in Czech Manufacturing Businesses - Svoboda, Ondřej (2024)
This study assesses the readiness of Czech manufacturing companies for the CS3D Directive, revealing a disparity in preparedness and highlighting the challenges faced by smaller firms due to inadequate processes and geographic disadvantages. The paper recommends that the public sector establish CS3D resource centers offering localized guidance and enhanced information dissemination. It also advises companies to integrate sustainability and human rights due diligence into their core operations. This involves leadership endorsement, comprehensive employee education, and fostering a culture of sustainability through transparent communication and active engagement. These initiatives not only ensure compliance with the Directive but also enhance companies' competitive advantage and reputation, positioning them as leaders in sustainable and ethical practices. The study underscores the necessity for adaptive strategies from both the public and private sectors to effectively meet the demands of the CS3D.